Investigating bifidobacteria and human milk oligosaccharide composition of lactating mothers. Issue 5 (19th March 2020) - Lugli, Gabriele Andrea; Duranti, Sabrina; Milani, Christian; Mancabelli, Leonardo; Turroni, Francesca; Alessandri, Giulia; Longhi, Giulia; Anzalone, Rosaria; Viappinai, Alice; Tarracchini, Chiara; Bernasconi, Sergio; Yonemitsu, Chloe; et al.
ABSTRACT: Human milk is known to carry its own microbiota, of which the precise origin remains obscure. Breastfeeding allows mother-to-baby transmission of microorganisms as well as the transfer of many other milk components, such as human milk oligosaccharides (HMOs), which act as metabolizable substrates for particular bacteria, such as bifidobacteria, residing in infant intestinal tract. In the current study, we report the HMO composition of 249 human milk samples, in 163 of which we quantified the abundance of members of the Bifidobacterium genus using a combination of metagenomic and flow cytometric approaches. Metagenomic data allowed us to identify four clusters dominated by Bifidobacterium adolescentis and Bifidobacterium pseudolongum, Bifidobacterium crudilactis or Bifidobacterium dentium, as well as a cluster represented by a heterogeneous mix of bifidobacterial species such as Bifidobacterium breve and Bifidobacterium longum . Furthermore, in vitro growth assays on HMOs coupled with in silico glycobiome analyses allowed us to elucidate that members of the Bifidobacterium bifidum and B. breve species exhibit the greatest ability to degrade and grow on HMOs. Altogether, these findings indicate that the bifidobacterial component of the human milk microbiota is not strictly correlated with their ability to metabolize HMOs. Abstract : In the current study, we quantified the abundance of members of the Bifidobacterium genus in 163 human milk samples using a combination of metagenomic and flow cytometry approaches.